2021
DOI: 10.1186/s12879-021-05946-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic maternal hepatitis B virus infection and pregnancy outcome- a single center study in Kunming, China

Abstract: Background Chinese population has a high prevalence of chronic hepatitis B virus (HBV) infection, the impact of which on pregnancy outcome remains controversial. A single-center retrospective cohort study was performed in Kunming, a multi-ethnic city in south-western China to examine this issue. Methods The singleton pregnancies delivering at ≥28 weeks gestation under our care in 2005–2017 constituted the study cohort. Maternal characteristics and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…In this study, we investigated the outcomes of 735 pregnant women with HBsAg carrier status and 18 693 cases in a non-exposed group of subjects in Hangzhou, China. We found that the proportion of positive maternal HBsAg carrier was 3.78%; this was slightly higher than the 3.3% rate reported previously in Kunming, China [ 18 ].…”
Section: Discussioncontrasting
confidence: 74%
“…In this study, we investigated the outcomes of 735 pregnant women with HBsAg carrier status and 18 693 cases in a non-exposed group of subjects in Hangzhou, China. We found that the proportion of positive maternal HBsAg carrier was 3.78%; this was slightly higher than the 3.3% rate reported previously in Kunming, China [ 18 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Three studies (sample size 94,525) indicated that compared to those with HBsAg negative, HBsAg positive women were older ( 16 , 49 , 52 ). Two studies (sample size 132,254) demonstrated that the age was not statistically different between HBsAg positive and negative groups ( 32 , 48 ).…”
Section: Resultsmentioning
confidence: 97%
“…Ten studies analyzed the relationship between the times of gestation and parity and HBsAg positive rate. Seven studies (sample size 954,199) suggested that HBV prevalence in primigravida and primiparas was lower ( 12 , 13 , 28 , 32 , 48 , 49 , 52 ), while the other three studies (sample size 45,248) showed no relevance ( 16 , 33 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 Similar to other reports, the prevalence of HBV infection was significantly lower in Liaoning (3.08%), 24 Tianjin (3.77%), 25 Shanxi (4.90%), 26 Xinjiang (4.43%), 26 Sichuan (4.24%), 27 and Yunnan (3.28%). 28 The prevalence rate of HBV infection differed among pregnant women in the provinces of China and at different periods. Moreover, recent national epidemiological data showed that the prevalence of HBV infection continuously declined among pregnant women in China.…”
Section: Discussionmentioning
confidence: 99%